Lycopene content and antioxidant capacity of portuguese watermelon fruits - Pinto, Paula (2011)
Red flesh watermelon is one of the main food sources with lycopene as the most abundant carotenoid and has been associated with a lowered risk of prostate cancer. In order to assess health benefits of Portuguese watermelon, five acessions from the Portuguese Bank of Germplasm were were chosen for antioxidant quantification and total solids content. Two of the acessions were further characterized for lycopene content. Due to its lycopene and antioxidant contents, accession 6185 may be considered a valuable germplasm for breeding programmes. The intake of one to three wedges of 6185 watermelon accession would provide between 6 to 18 mg of lycopene and 0.18 to 0.54 mmol TEAC (Trolox Equivalent Antioxidant Capacity), which might protect from prostate cancer and other oxidative stress related diseases.